Ionic liquids as a novel class of electrolytes in polymeric aqueous biphasic systems - Santos, Joao H. P. M.
The use of ionic liquids (ILs) as electrolytes in aqueous biphasic systems (ABS) composed exclusively of polymers and their application to the extraction of biomolecules is here studied. The binodal curves of the quaternary systems formed by polyethylene glycol (PEG 8000), sodium poly(acrylate) (NaPA 8000), water and ILs or inorganic salts as electrolytes are established. These systems enable the assessment of the influence of the salt nature, chemical structure and concentration on the two-phase formation. These systems were characterized regarding the pH and the ILs' partition between both phases. Moreover the extractive potential of these ABS is evaluated using the protein cytochrome c (Cyt c) and the dye chloranilic acid (CA). The main results on the extraction efficiencies show that Cyt c is recovered in the NaPA 8000-rich phase (EEcyt c >96.13 +/- 3.22%), while CA preferentially migrates towards the PEG 8000-rich phase (EECA >80.13 +/- 1.45%). The optimal electrolyte concentration in the CA partition was found to be the lowest possible, i.e. 0.1 wt%, as it leads to a remarkable increase in the partition coefficient of CA (K-CA) towards the PEG 8000-rich phase. These results indicate that this class of polymeric ABS may be an advantageous tool in the development of novel extractive platforms. (C) 2015 Elsevier Ltd. All rights reserved.